RETRACTION Septiantoko, R., Murdiono, M., Saliman, S., Setyawan, H., García-Jiménez, J. V.., Latino, F., Tafuri, F., Pranoto, N. W., Kurniawan, A. W., Anam, K., Shidiq, A. A. P., Rahmatullah, M. I., & Eken, Özgür. (2024). Diferencias en el rendimiento en los resultados del aprendizaje de educación física para estudiantes de secundaria según la ocupación de los padres: análisis de las diferencias en el estatus social de los padres al proporcionar motivación para el aprendizaje (Differences in Achievement in Physical Education Learning Outcomes for High School Students Based on Parental Occupation: Analysis of Differences in Parental Social Status in Providing Learning Motivation). Retos, 55, 882–888. https://doi.org/10.47197/retos.v55.105980 - RETOS, RETOS (Retos, 2025)
Septiantoko, R., Murdiono, M., Saliman, S., Setyawan, H., García-Jiménez, J. V.., Latino, F., Tafuri, F., Pranoto, N. W., Kurniawan, A. W., Anam, K., Shidiq, A. A. P., Rahmatullah, M. I., & Eken, Özgür. (2024). Diferencias en el rendimiento en los resultados del aprendizaje de educación física para estudiantes de secundaria según la ocupación de los padres: análisis de las diferencias en el estatus social de los padres al proporcionar motivación para el aprendizaje (Differences in Achievement in Physical Education Learning Outcomes for High School Students Based on Parental Occupation: Analysis of Differences in Parental Social Status in Providing Learning Motivation). Retos, 55, 882–888. https://doi.org/10.47197/retos.v55.105980Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 11Authors in the published PDF with modified authors: 13Differences between the authors between both moments: +5 y -3 (Additions: Riko Septiantoko, Francesca Latino, Francesco Tafuri, Nuridin Widya Pranoto, Özgür Eken. Eliminated: Ratko Pavlovic, Agnieszka Magdalena Nowak, Nugroho Susanto)